Novel biallelic OTOGL mutations in a Chinese family with moderate non-syndromic sensorineural hearing loss. Issue 6 (June 2015) - Gu, Xiaodong; Sun, Shan; Guo, Luo; Lu, Xiaoling; Mei, Honglin; Lai, Chuijin; Li, Huawei
Abstract: Objective: Autosomal recessive non-syndromic hearing loss (DFNB) is a genetically heterogeneous disorder. So far, 55 pathogenic genes have been identified. In this study, we aim to characterize the clinical feature and the genetic cause of a Chinese DFNB family. Methods: Whole exome sequencing was performed on the proband. Co-segregation between the hearing loss phenotype and the potential causative mutations was verified in all family members by Sanger sequencing. Results: Audiologic profiles of the affected family members revealed a moderate hearing loss mainly affecting higher frequencies. Novel biallelic OTOGL mutations, c.6467C>A (p.Ser2156*) and c.6474dupA (p.Ser2159Metfs*2), were identified in this family segregating with the childhood onset DFNB. Both mutations were predicted to cause either nonsense mediated mRNA decay or premature terminations of protein synthesis. Conclusions: We identified novel biallelic OTOGL mutations in a Chinese DFNB family. To the best of our knowledge, this is the first report of OTOGL mutations causing hearing loss in the East Asian population. Our finding enriched the mutation spectrum of OTOGL associated hearing loss.